2017
DOI: 10.1016/j.jfda.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interactions of herbal medicines for the treatment of chronic hepatitis

Abstract: Chronic liver disease is a serious global health problem, and an increasing number of patients are seeking alternative medicines or complementary treatment. Herbal medicines account for 16.8% of patients with chronic liver disease who use complementary and alternative therapies. A survey of the National Health Insurance Research Database in Taiwan reported that Long-Dan-Xie-Gan-Tang, Jia-Wei-Xia-Yao-San, and Xiao-Chai-Hu-Tang (Sho-saiko-to) were the most frequent formula prescriptions for chronic hepatitis use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 81 publications
0
13
0
1
Order By: Relevance
“…The oral administration of loganin described in this study was characterized by a non-invasive therapeutic approach in comparison to that of previous reports [40], which regarded loganin as an oral therapeutic agent against osteoarthritis. In addition, regarding the pharmacologic efficacy and drug bioavailability, metabolomic profiles, such as plasma concentration, should be used to evaluate drug properties [41]. The plasma concentrations of loganin were eliminated within 4 h after oral administration of loganin.…”
Section: Discussionmentioning
confidence: 99%
“…The oral administration of loganin described in this study was characterized by a non-invasive therapeutic approach in comparison to that of previous reports [40], which regarded loganin as an oral therapeutic agent against osteoarthritis. In addition, regarding the pharmacologic efficacy and drug bioavailability, metabolomic profiles, such as plasma concentration, should be used to evaluate drug properties [41]. The plasma concentrations of loganin were eliminated within 4 h after oral administration of loganin.…”
Section: Discussionmentioning
confidence: 99%
“…Since herbal products have been shown to have therapeutic properties and because their use has become more prevalent in the context of chronic liver disease, the safety of combined treatment with herbal products and conventional medicines should not be ignored. Previous articles revealed possible herb-drug interactions of traditional herbal formulas for chronic hepatitis with conventional drugs [29,30]. For instance, herbal products could delay the elimination of 5-FU in blood or change the bioavailability of carbamazepine [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…5 Various herbal medicines, including formula, extracts and compounds derived from herbs, have been used for treatment of liver diseases, including chronic hepatitis B, chronic hepatitis C (CHC), alcoholic liver disease, and nonalcoholic fatty liver disease. [6][7][8][9][10][11] Over the past few decades, particular attention has been paid to the potential anti-HCV effects of herbal medicines, and most of in vitro (in hepatic cell lines) and in vivo (in animals) studies have shown significant anti-HCV effects for a number of herbal medicines.…”
Section: Introductionmentioning
confidence: 99%